2011
DOI: 10.1016/j.jash.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous hydralazine for blood pressure management in the hospitalized patient: its use is often unjustified

Abstract: Background Intravenous hydralazine is approved for the treatment of hypertensive emergency and widely used for hypertension associated with toxemia of pregnancy. As we had observed increased off-label use of this agent in area hospitals, we studied its use in a University teaching hospital. Methods Patients were identified prospectively between April and October 2010 from all hospitalized patients who had an order for intravenous hydralazine entered into the computerized physician order entry system. Clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 12 publications
1
52
0
Order By: Relevance
“…In addition to there being no proven clinical benefit in this setting, the use of unnecessary IV antihypertensives is associated with unnecessary risks and excess cost. Another report of IV hydralazine in asymptomatic patients found that 17 of 94 patients experienced an adverse effect after administration . Not only is the drug acquisition cost for IV antihypertensives greater than their oral counterparts, often by a factor of 10 to 100, the intravenous route requires additional care to monitor their effects, adding to the human resource expense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to there being no proven clinical benefit in this setting, the use of unnecessary IV antihypertensives is associated with unnecessary risks and excess cost. Another report of IV hydralazine in asymptomatic patients found that 17 of 94 patients experienced an adverse effect after administration . Not only is the drug acquisition cost for IV antihypertensives greater than their oral counterparts, often by a factor of 10 to 100, the intravenous route requires additional care to monitor their effects, adding to the human resource expense.…”
Section: Discussionmentioning
confidence: 99%
“…Another report of IV hydralazine in asymptomatic patients found that 17 of 94 patients experienced an adverse effect after administration. 18 Not only is the drug acquisition cost for IV antihypertensives greater than their oral counterparts, often by a factor of 10 to 100, the intravenous route requires additional care to monitor their effects, adding to the human resource expense. Finally, the onset of action of intravenous agents is generally more rapid, which increases the risk of inducing hypotension and therefore targetorgan ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study, only 2.9 % of hospitalized patients treated with IV hydralazine or labetalol for HTN had evidence of diseases caused by hypertensive damage [21]. Similarly, a separate study also looking at the use of IV hydralazine showed only 2 % of treated patients showed signs of hypertensive emergency, and 8 % of patients experienced adverse events [62]. Intravenous hydralazine seems to be a drug of choice in many of these patients, perhaps because of ease of access on most non-ICU medical wards [63].…”
Section: Approach To Asymptomatic Elevated Bp In the Hospital Settingmentioning
confidence: 99%
“…There is increasing concern about the use of IVAH as well as the increased use of these agents in treating asymptomatic hypertension without any established guidelines about when and when not to use them 8 9. Clinical evidence thus far recommends conservative management of asymptomatic hypertension in the hospital setting with observation, oral antihypertensive medication and outpatient follow-up with a primary care provider 10…”
Section: Introductionmentioning
confidence: 99%